Manipulation of the Rkky Exchange by Voltages - Altbir-Drullinsky, D; Retamal-Abarzua, J (American Physical Society, 2019)
In the last years, electric fields have been used to control the magnetic exchange interactions and anisotropies in nanometric devices. In this paper, we study the spin-spin exchange interaction between two magnetic impurities embedded in a three-dimensional nonrelativistic electron gas, namely the Ruderman-Kittel-Kasuya-Yosida (RKKY) interaction. The gas is confined in an insulating structure, and an applied voltage produces local changes in the electron density, which modulates the Fermi level of the system. Using a simple model, we demonstrate that this voltage modifies the strength and wavelength of the coupling between the impurities. Depending on the voltage, the effective RKKY exchange can change from a ferro- to an antiferromagnetic coupling, and vice versa. The spin-spin coupling can also be switched on and off by the voltage. © 2019 American Physical Society.